Non-pest prey do not disrupt aphid predation by a web-building spider. Issue 1 (20th November 2015) - Welch, K.D.; Whitney, T.D.; Harwood, J.D.
Abstract: A generalist predator's ability to contribute to biological control is influenced by the decisions it makes during foraging. Predators often use flexible foraging tactics, which allows them to pursue specific types of prey at the cost of reducing the likelihood of capturing other types of prey. When a pest insect has low nutritional quality or palatability for a predator, the predator is likely to reject that prey in favour of pursuing alternative, non-pest prey. This is often thought to limit the effectiveness of generalist predators in consuming aphids, which are of low nutritional quality for many generalist predators. Here, we report behavioural assays that test the hypothesis that the generalist predator, Grammonota inornata (Araneae: Linyphiidae), preferentially forages for a non-pest prey with high nutritional quality (springtails), and rejects a pest prey with low nutritional quality (aphids). In no-choice assays, molecular gut-content analysis revealed that spiders continued to feed on the low-quality aphids at high rates, even when high-quality springtails were readily available. When provided a choice between aphids and springtails in two-way choice tests, spiders did not show the expected preference for springtails. Decision-making by spiders during foraging therefore appears to be sub-optimal, possibly because of attraction to the less frequently encountered of two preys as part of a dietary diversification strategy. These results indicate that behavioural preferences alone do not necessarily compromise the pest-suppression capacity of natural enemies: even nutritionally sub-optimal pest prey can potentially be subject to predation and suppression by natural enemies.